A TIME LIMIT FOR URBAN LAND REGULARIZATION IN PERMANENT PRESERVATION AREAS: THE LEGAL ECONOMIC AND BEHAVIORAL ANALYSIS AND ENVIROMENTAL PROTECTION - Tabak, Benjamin Miranda (2023)
This article sets the timeframe that limits the possibility of urban land regularization in areas of permanent preservation, forecasted by the New Forest Code, covering normative, economic and behavioral analyses of the relevant legal standards. First, the principles that influence the interpretation of environmental standards and the legislative development frame on the subject are outlined. After that, enlarging the approach with a focus on concrete effects expected from the application of the legislation, the economic analysis is used, working on the idea of incentives and the concepts of cheap talk and moral hazard. Finally, the behavioral analysis based on radical behaviorism provides the theoretical basis to link the different normative interpretations and how they influence the behavior of those who are affected, seeking for appropriate environmental protection. Thus, the combination of such theoretical references allows for understanding the legal milestone that best conciliates environmental protection, mitigating the risk of further degradation arising from the illegal occupation process, providing greater legal assurance to those who now occupy non-buildable areas.